PENERAPAN PROFILE MATCHING UNTUK SELEKSI ASISTEN LABORATORIUM - Sri Rahayu Astari; Rusydi Umar; Sunardi Sunardi (Telematika, 2019)
AbstractLaboratory assistants in universities are usually active students who are recruited to help lecturers implement theoretical courses given by lecturers in class. Assistant recruitment is carried out to screen students who have talent in teaching, because in addition to assisting lecturers in providing practical material, becoming an assistant is a way to measure personal abilities that have talent in teaching. This study applies the profile matching method by determining the gap value which is the difference between the candidate values and the standard that has been set between the profile data from the selected assistant candidates. The purpose of applying this profile matching method is to get an assistant that is in accordance with the main and supporting factors that the reviewer will determine in each selection. Calculation using the profile matching method gives different weights to each criterion, so that the criteria have weights according to the type or standard of interest. This study uses a prototype method that involves the user in the analysis process. This study resulted in a calculation method using the profile matching method by determining each criterion weight, then classifying or dividing criteria into core factors and secondary factors which ultimately resulted in the total amount of the whole, and then ranking.Keywords : Assistant, Profile Matching, decision making, core factors, secondary factors.Asisten laboratorium di perguruan tinggi biasanya merupakan mahasiswa aktif yang direkrut untuk membantu dosen mengimplementasikan mata kuliah teori yang diberikan dosen dikelas. Rekrutmen asisten dilakukan untuk menyaring mahasiswa yang memiliki bakat dalam mengajar, karena selain untuk membantu dosen dalam memberikan materi praktikum, menjadi asisten adalah cara untuk mengukur kemampuan personal yang memiliki bakat dalam mengajar. Penelitian ini menerapkan metode profile matching dengan menentukan nilai gap yang merupakan selisih nilai calon dengan standar yang sudah ditetapkan antara profil data dari calon asisten yang diseleksi. Tujuan dari penerapan metode profile matching ini adalah untuk mendapatkan asisten yang sesuai dengan faktor utama dan pendukung yang akan ditentukan reviewer setiap seleksi dilakukan. Perhitungan menggunakan metode profile matching memberikan bobot berbeda pada setiap kriteria, agar kriteria mempunyai bobot sesuai dengan tipe atau standar kepentingannya. Penelitian ini menggunakan metode prototype yang melibatkan user dalam proses analisis. Penelitian ini menghasilkan cara perhitungan menggunakan metode profile matching dengan menentukan setiap bobot kriteria, kemudian mengelompokkan atau membagi kriteria menjadi core factor dan secondary factor yang akhirnya menghasilkan jumlah total dari keseluruhan, dan kemudian dilakukan perankingan.Kata Kunci : Asisten, Profile Matching, pengambilan keputusan, core factor, secondary factor